Optimal liquidation in dark pools - Peter Kratz; Torsten Schöneborn (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
We consider a large trader seeking to liquidate a portfolio using both a transparent trading venue and a dark pool. Our model captures the price impact of trading in transparent traditional venues as well as the execution uncertainty of trading in a dark pool. The unique optimal execution strategy uses both venues continuously. The order size in the dark pool can over- or underrepresent the portfolio size depending on adverse selection and the correlation structure of the assets in the portfolio. Introduction a dark pool results in delayed trading at the traditional venue. The appeal of the dark pool is increased by liquidity but reduced by adverse selection. By pushing up prices at the traditional venue and parallel selling in the dark pool, a trader might generate profits; we provide sufficient conditions to rule out such profitable price manipulation strategies.
Keywords: C02; C61; G11; 330; dark pools; optimal liquidation; adverse selection; market microstructure; illiquid markets; Wertpapierhandel; Manipulation; Börsenkurs; Marktliquidität; Mikrostrukturanalyse; Theorie